2022
DOI: 10.2196/32499
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Demographic Characteristics of Users of a Free Tobacco Cessation Smartphone App: Observational Study

Abstract: Background Tobacco use continues to be the leading preventable cause of death, disease, and disability in the United States. Since 2000, Washington state has offered free tobacco “quitline” services to help its residents stop using tobacco. In 2015, the state began offering free access to a tobacco cessation smartphone app to absorb excess quitline demand. Since most publicly funded tobacco cessation programs are designed to provide access to populations disproportionately impacted by tobacco use, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We assessed participants' age, sex, race, ethnicity, annual pretax household income, highest level of education, whether they had children younger than 18 years living in the home, and whether they lived in a rural or nonrural area, as determined by zip code (20).…”
Section: Independent Variablesmentioning
confidence: 99%
“…We assessed participants' age, sex, race, ethnicity, annual pretax household income, highest level of education, whether they had children younger than 18 years living in the home, and whether they lived in a rural or nonrural area, as determined by zip code (20).…”
Section: Independent Variablesmentioning
confidence: 99%
“…In contrast to older smokers, younger individuals with higher level of education were more likely to use mobile applications for SC. Fradkin et al 11 analyzed the demographic characteristics of 1280 registered and activated adult users of a free tobacco cessation smartphone app, and their study revealed that 57.5% (682/1186) of the app users were <45 years, and 93.7% (1145/1222) had a high school education or higher.…”
Section: Introductionmentioning
confidence: 99%